Understanding public places incorporating conception, activities and physical attributes in developing a space efficient public market - Laniba, Christine C.; Malaque, Isidoro I., III (2017)
Alongside the undeniable importance of public markets in the country, there are several issues concerning the structure that the users still face. Using Canter?s Theory of place, this research analyzed the social and spatial characteristics of markets by understanding the relationship between the conception, physical attributes, and activities of the markets and how it affects the space efficiency of the place. The study aim to collect the data that could determine the space efficient of public markets by using the Fuzzy Logic method and other tools. Through qualitative and quantitative research, four markets of three cities in Southern Mindanao namely, Tagum Public Market, Panabo Premium Market, Bankerohan Public Market, and Agdao Public Market were studied. Data and results were assessed over descriptive numerical measures from interviews and surveys. Also, the results attained were analyzed to better understand how the architectural characteristics affect the movement of users inside the market. Provision of strategies in market planning was also derived from the output.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2017